2020
DOI: 10.1016/j.ocarto.2020.100119
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of transient receptor potential canonical 5 (TRPC5) in osteoarthritis

Abstract: Introduction Osteo-arthritis (OA) involves joint degradation and usually pain; with mechanisms poorly understood and few treatment options. There is evidence that the transient receptor potential canonical 5 (TRPC5) mRNA expression is reduced in OA patients’ synovia. Here we examine the profile of TRPC5 in DRG and involvement in murine models of OA. Design TRPC5 KO mice were subjected to partial meniscectomy (PMNX) or injected with monoiodoacetate (MIA) and pain-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…We show that EA reduced thermal and mechanical hyperalgesia in the carrageenan model. This was in accordance with previous data from this laboratory that showed that TRPC5 expression had a protective role in inflammation-and pain-related behaviour, secondary to the development of experimental arthritis [4,5]. To examine the hypothesis that TRPC5 was mediating the EA effect in vivo, we tested TRPC5 KO mice in the carrageenan model and observed that neither the anti-inflammatory nor the analgesic effects were mediated through TRPC5.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We show that EA reduced thermal and mechanical hyperalgesia in the carrageenan model. This was in accordance with previous data from this laboratory that showed that TRPC5 expression had a protective role in inflammation-and pain-related behaviour, secondary to the development of experimental arthritis [4,5]. To examine the hypothesis that TRPC5 was mediating the EA effect in vivo, we tested TRPC5 KO mice in the carrageenan model and observed that neither the anti-inflammatory nor the analgesic effects were mediated through TRPC5.…”
Section: Discussionsupporting
confidence: 88%
“…It was previously shown in TRPC5-transfected cells in culture that EA could induce the calcium uptake, in a dosedependent manner [8]. We have previously demonstrated that dorsal root ganglia express TRPC5 channels [5]. Here, we quantified the accumulation of cobalt in cultured DRG neurons induced by EA stimulation.…”
Section: Ea Induces Trpc5 Independent Cobalt Uptake In Cultured Dorsal Root Ganglia (Drg) Neuronsmentioning
confidence: 91%
See 3 more Smart Citations